The importance of the student wellness in the new teaching/learning process - Trujillo-Aguilera, Davinia; Pozo-Ruz, Ana; Sánchez-Rodríguez, José; Martín Graciani, María Olvido (My University, 2014)
Nowadays, the European Higher Education Area means an important change in the teaching/learning process: it is necessary to involve more efficiently to the students. Moreover, university education has undergone a significant change to new models that encourage the active role of students in the teaching/learning process. This new framework includes the increase in the development and use of new Information and Communication Technology in education and the analysis of the academic performance of students and their sensation of engagement and burnout. In the case study in this paper, a new teaching methodology is implemented and it is based on a kit of new software interactive tools for Power Electronics. The main objective of this experience consists of the design, development and implementation of a new multimedia resources in order to use them in the teaching/learning process of the subject. To evaluate the benefits and drawbacks of this new methodology and the compliance with the objectives, several surveys have been designed, for both students and lecturers. These results are complemented with the study of the student stress levels, information that will be complemented with an in-depth analysis of the got marks of the students and with the sensation of engagement and burnout, measured in terms of academic stress.
Keywords: Enseñanza superior - Innovaciones tecnológicas; Power Electronics; Teaching/Learning process; Multimedia tools; Educational software evaluation; E-learning; Burnout; Engagement; Academic stress